Sri Lanka : Overview of Tobacco Use, Tobacco Control Legislation and Taxation - World Bank Group (World Bank, Washington, DC, 2019)
Sri Lanka ratified the Framework Convention on Tobacco Control in 2003 and implemented some comprehensive tobacco control policies. From June 1, 2015, health warnings on cigarette packages in Sri Lanka have to cover 80 percent of the large sides. In 2005-2006, about 38.0 percent of men and less than 1 percent of women were current tobacco smokers in Sri Lanka. The prevalence smoking among men was about 40 percent in 2005-2006 and decreased to about 32 percent in 2009-2014. The volumes of cigarette production in Sri Lanka were fairly steady at the level of 5.2 billion sticks in the late 1990s, and then the production gradually decreased to about 4 billion cigarettes in 2013-2016. The government has the power to change excise tax rates several times a year. The taxation system used for cigarettes is 5-tier specific. In 2005-2015, excise rates for most tiers were increased by more than 300 percent; however, the inflation rate for those eleven years combined was 260 percent; so, real cigarette prices did not change much. In late 2014, the VAT liability on cigarettes was temporarily removed. For two years, excise was the only tax levied on cigarettes in Sri Lanka. While the excise rates were increased in 2014, the overall tax burden almost did not change. Such a shift between VAT and excise tax was the main factor of the excise revenue increase by 40 percent in 2015 as excise revenue mainly replaced VAT revenue. The largest changes in cigarette taxation in Sri Lanka took place in October-November 2016: (1) Excise rates were increased by 26-28 percent for two higher tiers, by 37-40 percent for two middle ties, and by 67 percent for the lowest tier; (2) The VAT rate was increased from 12 percent to 15 percent, and cigarettes were again made liable for VAT. However, after the increase in cigarette tax burden in late 2016, in the first four months of 2017, the excise revenue from cigarettes and tobacco products declined by 17 percent, and cigarette production decreased by 31 percent. The VAT-excise reverse shift was the main factor of excise revenue reduction in early 2017. The VAT revenue increased, and its increase was larger than the reduction in the excise revenue. Another factor of revenue decline in early 2017 was forestalling: tobacco industry overproduced cigarettes to pay taxes before tax increases. Another factor behind cigarette sales reduction in Sri Lanka was the pricing policy of the tobacco industry.